Self-Study Courses on Physical Training and Sports Activities in the Conditions of Credit-Modular System of Teaching - Valiyeva Elmira Valiyevna; Kholikov Akmal Tojidinovich, (Peerian Journals Publishing, 2022)
Year by year various forms of physical exercises appear and develop and new physical activities and exercises are improved. The article presents the results of studies of stu-dents’ preferences in the choice of different means of physical culture and sport to better health outcomes and the formation of physical culture of the individual
Keywords: means of physical culture and sports activities; physical education of the individu-al, level of health